Electrical support during outdoor cycling in patients with coronary artery disease: impact on exercise intensity, volume and perception of effort. Issue 4 (4th July 2018) - Hansen, Dominique; Soors, An; Deluyker, Valerie; Frederix, Ines; Dendale, Paul
Abstract: Background: Electrical assisted bicycles (EAB's) could be used to overcome barriers and difficulties to outdoor cycling and thus assist in achieving a sufficient physical activity level in coronary artery disease (CAD) patients, but it is unknown whether sufficient exercise intensities and volumes could be elicited during cycling on EAB's. In this study we examined, for the first time, the acute physiological impact of electrical support during outdoor cycling in CAD patients (ISRCTN32238279). Methods: Fifteen CAD patients (13 males), aged 64 ± 7 years executed a maximal cardiopulmonary exercise test and afterwards cycled a predefined outdoor route of 10 km, in three different conditions: classical cycling (no support), EAB with low support (EABlow ) and high support (EABhigh ). Oxygen uptake (VO2 ) and carbon dioxide output (VCO2 ) was measured continuously by a portable gas-analysing system. Cycling time was recorded and ratings of perceived exertion (RPE) was assessed at 3 and 7 km. Results: Mean VO2 during EABhigh (1721 ± 537 mlmin −1 ) was significantly lower compared to EABlow (1890 ± 619 mlmin −1, p  < .05), but no differences were found between EABlow and classical cycling (1846 ± 523 mlmin –1 ). EABlow and EABhigh elicited a sufficient volume and intensity (6.6 ± 2.0 MET's (74 ± 6% VO2peak ) and 6.0 ± 1.8 MET's (68 ± 7% VO2peak ), respectively) to adhere to the guidelines for secondary prevention in CAD. RPE was significantly lower p  < .05) during EABhigh (9 ± 2), than during EABlow (11 ± 2) or classical cycling (11 ± 2). Conclusions: Outdoor cycling with electrical support leads to a sufficiently high exercise intensity and volume in CAD patients, and may be considered as an alternative exercise modality.